On Micro - b ̇ - open sets and Micro - b ̇ - continuity - Taha H. Jasim; Marwah D. Sultan (Tikrit Journal of Pure Science, 2020)
The purpose of this research is generalize the concepts of micro  openset, so we study the relation this new concept open set micro-pre-open set, micro-semi-open set, micro  open set, and micro openset and micro open continuity and micro  irresolute continuity in micro topological space and study the relationship among them, many theorems were proved as characteristic of these type of continuity and some examples were introduced.